Themes Familiar : Research and Display in the Primary School Using Everyday Objects - Booth, W.; Briten, P. and Scott, F. (Twickenham Belair, 1987)
Focuses on 15 cross-curricular topics including language, design, technology, music, mathematics, art and craft, environmental studies, stories and poems. Encourages children to research, discover, and create using everyday objects.
Include Colored Illustration
Keywords: Elementary school teaching